VERBALIZATION OF THE CONCEPT “PROSPERITY” IN THE SHORT STORY “WHILE THE AUTO WAITS” BY O.HENRY (Conferencea, 2022)
The object of the work is the concept of "prosperity". The concept of "prosperity" is the subject of the work. The research is about the meanings of lexical components in English that express the concept of "prosperity". The thesis theoretical value is that the contents can be utilized to prepare for Modern Linguistics and Literature classes, as well as while creating following scientific works. The practical value of this work is found in the ability to apply the findings and research materials in the field of fiction language, when preparing lectures and practical classes on language theory, text linguistics, general and comparative linguistics, cultural linguistics, in the development of diploma and term paper topics, and in the teaching of intercultural communication. The materials investigated in this research is the short story “While the Auto Waits” by O. Henry. The methods of analysis of the work are conceptual analysis. The linguocultural features of the concept “prosperity” in English fictional texts have been defined through analysis of the verbalization of the concept in short stories about American society towards this issue. Concept has a significant role in studying culture, society, and human beings. Description and analysis of concepts can provide a key to a deeper understanding of the native culture and language.